2015
DOI: 10.1038/srep15396
|View full text |Cite
|
Sign up to set email alerts
|

Caerulomycin A inhibits Th2 cell activity: a possible role in the management of asthma

Abstract: We have recently demonstrated that Caerulomycin A induces regulatory T cells differentiation by suppressing Th1 cells activity. The role of regulatory T cells is well established in suppressing the function of Th2 cells. Th2 cells are known to inflict the induction of the activation of asthma. Consequently, in the present study, we monitored the influence of Caerulomycin A in inhibiting the activity of Th2 cells and its impact in recuperating asthma symptoms. Interestingly, we observed that Caerulomycin A sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 46 publications
(51 reference statements)
0
27
0
Order By: Relevance
“…Stained sections were analyzed under a light microscope (Axio Imager M1; Carl Zeiss, Oberkochen, Germany). The degree of lung inflammation and goblet cell hyperplasia was scored on a subjective scale of 0 to 4 as previously described [18]. Briefly, to score the inflammatory cell infiltration in the intraluminal, alveolar, peribronchial, and perivascular regions, cell counts were performed blind based on five point grading system for the following features: 0: normal, 1: few cells, 2: a ring of inflammatory cells 1 cell layer deep; 3: a ring of inflammatory cells 2-4 cells deep, 4: a ring of inflammatory cells of > 4 cells deep.…”
Section: Methodsmentioning
confidence: 99%
“…Stained sections were analyzed under a light microscope (Axio Imager M1; Carl Zeiss, Oberkochen, Germany). The degree of lung inflammation and goblet cell hyperplasia was scored on a subjective scale of 0 to 4 as previously described [18]. Briefly, to score the inflammatory cell infiltration in the intraluminal, alveolar, peribronchial, and perivascular regions, cell counts were performed blind based on five point grading system for the following features: 0: normal, 1: few cells, 2: a ring of inflammatory cells 1 cell layer deep; 3: a ring of inflammatory cells 2-4 cells deep, 4: a ring of inflammatory cells of > 4 cells deep.…”
Section: Methodsmentioning
confidence: 99%
“…MQ22, and Streptomyces californicus . Caerulomycin A, possessing 4- O -methyl and 6- E -aldoxime groups, is known to act as an antibiotic [ 15 ], anti-asthma agent [ 20 ], and immunosuppressive agent [ 21 ]. Caerulomycin C, which has 3,4-di- O -methyl and 6- E -aldoxime groups, showed similar antibiotic activity [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…The broad antifungal activity of caerulomycin A has been extensively reported (Chatterjee et al, 1984, Ambavane et al, 2014). Other studies have suggested the important role of caerulomycin A in the regulation of immune homeostasis (Gurram et al, 2014, Kujur et al, 2015). Product 3 (caerulomycin F) presented the same activity spectrum as the two new cyanogrisides, while product 5 (caerulomycinonitrile) has the lowest activity.…”
Section: Discussionmentioning
confidence: 97%
“…At the time of writing, 9 cyanogrisides and 13 caerulomycins have been isolated and characterized. These compounds have been shown to have antibacterial, antifungal, antiparasitic and antitumor activities (Funk and Divekar, 1959, Chatterjee et al, 1984, Ambavane et al, 2014, Kujur et al, 2015).…”
Section: Introductionmentioning
confidence: 99%